PELATIHAN PEMBUATAN GAME EDUCAPLAY UNTUK MENINGKATKAN KREATIVITAS BELAJAR SISWA - Romundza, Febbry; Afrida, Afrida; Novferma, Novferma; Miharti, Izra; Dewi, Nurmala; Sasih, Agustin Wela (STKIP Persada Khatulistiwa Sintang, 2025)
ABSTRACT : The use of interactive learning media is one of the strategies to enhance students’ creativity and motivation in the digital era. One platform that can be utilized is Educaplay, which allows users to easily and attractively create various types of educational games. This training activity aims to improve participants’ skills in designing learning games using Educaplay and to assess its impact on students’ learning creativity. The training methods included lectures, demonstrations, hands-on practice, and reflective discussions. The activity was conducted over three days and involved 30 participants, consisting of high school teachers and students. Evaluation was carried out through observation, assessment of game products, and questionnaires on satisfaction and effectiveness. The results showed that 90% of participants were able to create at least two types of educational games relevant to the learning material. The use of these games during trial learning sessions led to a 40% increase in student participation and creativity compared to conventional methods. Moreover, 87% of participants stated that the training was very useful in supporting learning innovation. In conclusion, game development training using Educaplay is effective in improving participants’ digital skills and in promoting students’ creativity in learning. This platform offers an innovative alternative for active and engaging 21st-century learning.Keywords : Educaplay, educational games, creativity, interactive media, training.ABSTRAK : Penggunaan media pembelajaran interaktif merupakan salah satu strategi untuk meningkatkan kreativitas dan motivasi belajar siswa di era digital. Salah satu platform yang dapat dimanfaatkan adalah Educaplay, yang memungkinkan pembuatan berbagai jenis game edukatif secara mudah dan menarik. Kegiatan pelatihan ini bertujuan untuk meningkatkan keterampilan peserta dalam merancang game pembelajaran menggunakan Educaplay serta mengukur dampaknya terhadap kreativitas belajar siswa. Metode pelatihan yang digunakan meliputi ceramah, demonstrasi, praktik langsung (hands-on), serta diskusi reflektif. Kegiatan dilaksanakan selama tiga hari dengan melibatkan 30 peserta yang terdiri dari guru dan siswa tingkat SMA. Evaluasi dilakukan melalui observasi, penilaian produk game, serta kuesioner kepuasan dan efektivitas. Hasil menunjukkan bahwa 90% peserta mampu membuat minimal dua jenis game edukatif yang sesuai dengan materi pembelajaran. Penggunaan game yang dihasilkan dalam uji coba pembelajaran menunjukkan adanya peningkatan partisipasi dan kreativitas siswa sebesar 40% dibandingkan dengan metode konvensional. Sebanyak 87% peserta menyatakan pelatihan ini sangat bermanfaat dalam mendukung inovasi pembelajaran. Kesimpulannya, pelatihan pembuatan game menggunakan Educaplay efektif dalam meningkatkan keterampilan digital peserta serta mampu mendorong kreativitas belajar siswa. Platform ini dapat menjadi alternatif media pembelajaran inovatif yang mendukung pembelajaran aktif dan menyenangkan di abad 21.Kata kunci : Educaplay, game edukatif, kreativitas, media interaktif, pelatihan